Variations of the Kuroshio in the Luzon Strait Revealed by EOF Analysis of Repeated XBT Data and Sea‐Level Anomalies. Issue 7 (28th June 2021) - Long, Yu; Zhu, Xiao‐Hua; Guo, Xinyu; Ji, Fei; Li, Zhiyuan
Abstract: The Kuroshio in the Luzon Strait (KLS) has long been a focus of research for its complex ocean dynamics; however, it is poorly understood owing to a lack of long‐term in situ observations. Empirical orthogonal function (EOF) analyses were applied to quarterly expendable bathythermograph data (XBT, with a spatial resolution of 10–20 km in the Kuroshio region and 33 km in the other regions) and sea‐level anomaly (SLA) data, to examine the variations of the KLS. The first EOF modes of water temperature and SLA represent seasonal variations. The volume transport of the KLS referring to a 700 m depth reaches its maximum in warm months (19.4 Sv, July–September) and its minimum in cold months (17 Sv, January–March). This variation is similar to that east of Taiwan but is opposite to that east of Luzon, although the Luzon Strait is only 2° distant from the area east of Luzon. The outflow (1.3 Sv) from the South China Sea (SCS) to the Kuroshio in the warm months and the Kuroshio intrusion into the SCS in the cold months are responsible for this seasonal contrast. The second EOF modes of water temperature and SLA are related to the latitudinal movement of the Kuroshio recirculation on a time scale of 2–24 months. Lag correlation and wavelet analysis demonstrate that this mode is triggered by the westward‐propagating SLA along 21°–24°N and is affected by the downstream propagation of low‐frequency variation (mostly annual to biennial) from the North Equatorial Current bifurcation area. Plain Language Summary: Variations of the Kuroshio in the Luzon Strait (KLS) from 1999 to 2010 were examined by using sea‐level anomaly (SLA) data and long‐term repeated water temperature data observed by expendable bathythermography (XBT, cast by automatic launchers equipped on commercial ships). The decomposition (empirical orthogonal function, EOF) analysis of the two datasets shows that the most dominant components represent seasonal variations. The volume transport of the KLS reaches a maximum in warm months (July–September) and a minimum in cold months (January–March), which is similar to the seasonal variation of the Kuroshio east of Taiwan but is opposite to that east of Luzon. The Kuroshio‐South China Sea (SCS) water exchange is the main cause of the reversed seasonal variation in the Kuroshio transport between the area east of Luzon and the Luzon Strait. The second dominant components represent the latitudinal movement of the Kuroshio recirculation and result from the westward‐propagating SLA along 21°–24°N and the downstream propagation of low‐frequency variation from the area where the North Equatorial Current bifurcates into the Kuroshio and Mindanao Current. This work has implications for the Kuroshio‐SCS water exchange and Kuroshio‐eddy interactions from east of Luzon to the east of Taiwan. Key Points: Variations of the Kuroshio in the Luzon Strait (LS) were examined by analyzing sectional water temperature and sea‐level anomaly data Kuroshio‐South China Sea water exchange contributes to the opposite seasonal variation in volume transport from east of Luzon to the LS Westward propagated eddies along 21°–24°N and variations from the North Equatorial Current bifurcation impact the Kuroshio in the LS